PENGARUH PERTUMBUHAN KREDIT PADA PROFITABILITAS DENGAN TINGKAT PERPUTARAN KREDIT SEBAGAI VARIABEL PEMODERASI - Rastiniyati, Ni Kadek; Ulupui, I G K A (E-Jurnal Akuntansi, 2015)
Bali provincial government's efforts in supporting the economic development of the rural communities with the LPD. LPD performance assessment can not be separated from its ability to generate earnings / profit. The purpose of this study was to determine the effect of credit growth to profitability with a turnover rate of credit as a moderating variable. This study used 342 samples using purposive sampling method. Analysis using multiple linear regression analysis. Based on tests that have been performed in this study shows that credit growth significantly influence profitability, turnover rate loans have a significant effect on profitability, while the turnover rate credit weakens the relationship between credit growth to profitability in Badung LPD 2011-2013.
Keywords: profitability, LDR, credit turnover